2019
DOI: 10.1016/j.celrep.2019.01.078
|View full text |Cite
|
Sign up to set email alerts
|

Hypothalamic Control of Conspecific Self-Defense

Abstract: SUMMARYActive defense against a conspecific aggressor is essential for survival. Previous studies revealed strong c-Fos expression in the ventrolateral part of the ventromedial hypothalamus (VMHvl) in defeated animals. Here, we examined the functional relevance and in vivo responses of the VMHvl during conspecific defense. We found that VMHvl cells expressing estrogen receptor α (Esr1) are acutely excited during active conspecific defense. Optogenetic inhibition of the cells compromised an animal’s ability to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
55
1
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(64 citation statements)
references
References 38 publications
7
55
1
1
Order By: Relevance
“…A smaller set of neurons showed changes in activity that were time-locked to individual defeat events (117/319, 36%, Defeat+; 36/319, 11%, Defeat-) when the intruder attacked the experimental animal ( Figure 1i-k ). These findings are consistent with earlier cFos and bulk calcium imaging studies (Motta et al, 2009; Sakurai et al, 2016; Wang et al, 2019) and confirm that VMHvl is strongly recruited during social defeat.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…A smaller set of neurons showed changes in activity that were time-locked to individual defeat events (117/319, 36%, Defeat+; 36/319, 11%, Defeat-) when the intruder attacked the experimental animal ( Figure 1i-k ). These findings are consistent with earlier cFos and bulk calcium imaging studies (Motta et al, 2009; Sakurai et al, 2016; Wang et al, 2019) and confirm that VMHvl is strongly recruited during social defeat.…”
Section: Resultssupporting
confidence: 92%
“…However, loss of function studies demonstrate that defensive responses to social threats do not depend on VMHdm, but rather require VMHvl, suggesting that the reproductive system plays a more general role in controlling both aggression and defense to social stimuli (Silva et al, 2013; Silva et al, 2016). Consistent with a general role in social threat responding electrical, pharmacogenetic, or optogenetic stimulation of VMHvl is able to elicit or increase the probability of social aggression (Olivier, 1977; Kruk et al, 1983; Lin et al, 2011; Lee et al, 2014; Hashikawa et al, 2017; Yang et al, 2017; Wang et al, 2019) and avoidance (Sakurai et al, 2016; Wang et al, 2019). However, these responses are often unreliable and have been shown to be influenced by the social and hormonal status of both the subject and the threat (Lin et al, 2011; Lee et al, 2014; Sakurai et al, 2016; Yang et al, 2017) suggesting a role for past experience or other environmental factors in dictating the behavioral output of VMHvl.…”
Section: Introductionmentioning
confidence: 71%
See 1 more Smart Citation
“…Interestingly, we found that activation of pSI -PAG neurons in a defeated mouse immediately shifted the defensive response pattern of the subordinate mouse to aggressive conspecifics – from defensive flight or freezing to robust attack (Figure 6). It should be noted that the behavior induced in a defensive mouse by stimulation of pSI neurons in the present study, which was characterized by robust attack, is rather different from the active defensive behavior induced by activation of the VMHvl, which is characterized by dashing and jumping away from the aggressor (Wang et al, 2019).…”
Section: Discussioncontrasting
confidence: 66%
“…Pharmacological manipulation of PAG circuits have been shown affect the efficacy of hypothalamic-mediated conspecific aggression, strongly indicating that the PAG’s actions are downstream of the hypothalamus (Zalcman and Siegel 2006; Gregg and Siegel 2003), though its precise role in this transformation has remained unclear. The emerging role of the PAG in the expression of other innate behaviors, such as stimulus-induced flight, appears to be that of a split-second action (Evans et al 2018; Wang et al 2019). We reasoned that a parallel circuit in the PAG might perform a similar function during conspecific attack.…”
mentioning
confidence: 99%